Metabolic disorders due to methanol poisoning - Salek, Tomas; Humpolicek, Petr; Ponizil, Petr (Biomedical papers, 2014)
Aim: The aim of this study is to compare markers of glomerular filtration rate (GFR), estimated GFR (eGFR), and metabolic parameters between admission and recovery in 13 patients of Tomas Bata hospital with methanol poisoning during methanol problems in the Czech Republic in 2012. The impact of methanol concentration and age on metabolic parameters were discovered at the time of admission to hospital.Materials and Methods: The serum osmolality, methanol, ethanol, creatinine, cystatin C, Troponin I, ALT, plasma pH and lactate were measured in these 13 patients. The eGFR from serum creatinine (creatnine eGFR) and from cystatin C (cystatin C eGFR) were also determined.Results: Increased serum osmolality and markers of metabolic acidosis are key indirect laboratory findings in patients with methanol poisoning. There were no significant changes in eGFR in our patients between admission and recovery. Increased serum troponin I concentration was confirmed as an indicator of myocardial necrosis in four patients. Two patients developed acute kidney injury (AKI) before admission.Conclusions: We found statistically significant differences in serum osmolality concentration, plasma pH and lactate between admission and recovery. We found no changes in eGFR between admission and recovery. One patient had vision problems due to damage to the occipital lobes. Methanol poisoning may cause increase in markers of cardiac damage.
Keywords: intoxication; osmolality; metabolic acidosis; creatinine; cystatin C